A new species of Mycomya Rondani, 1856 (Diptera: Mycetophilidae) common to southeast Australia, Tasmania, and New Zealand - Kerr, D. Steven; Thompson, Shaun; Kerr, Peter H. (Zootaxa, 2023)
Mycomya quadrimaculata sp. nov. is described from specimens collected in southeast Australia, Tasmania, and New Zealand. A key and type photographs of known Australian and New Zealand Mycomya species are provided. The relative abundance, observed distribution, and morphological affinities of the new species suggests that it is adventive and a recent introduction to New Zealand. Wing characters indicate that the new species is most closely aligned with a subgroup of the Australian Mycomya fauna.